2000
DOI: 10.1002/(sici)1521-4109(200005)12:7<535::aid-elan535>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Propranolol by Capillary Electrophoresis with End-Column Amperometric Detection

Abstract: A capillary electrophoresis-amperometric detection system was developed for the determination of propranolol (PRO) at a 33 mm carbon ®ber microdisk electrode (CFE). The cyclic voltammogram, the hydrodynamic voltammograms and the effect of pH were studied. Under the optimum conditions: separation voltage 15 kV; injection 3 s at 15 kV; 10 mM pH 7.5 phosphate buffer, 1.15 V (vs. Ag=AgCl) detection potential, the detection limit (LOD) for PRO was 0.05 mM (S=N 3). The response for PRO was linear over two orders of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Analogously, as for 4'OH PS, the relationship of log(I p ) vs. log(v) was examined. The dependence could be expressed by the equation: log (I p / µA) = 0.467 log (v / (mV s -1 )) -1.379 (8) with a correlation coefficient of R 2 = 0.9981. The value of the slope confirmed that the process is diffusion-controlled.…”
Section: Effect Of Scan Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Analogously, as for 4'OH PS, the relationship of log(I p ) vs. log(v) was examined. The dependence could be expressed by the equation: log (I p / µA) = 0.467 log (v / (mV s -1 )) -1.379 (8) with a correlation coefficient of R 2 = 0.9981. The value of the slope confirmed that the process is diffusion-controlled.…”
Section: Effect Of Scan Ratementioning
confidence: 99%
“…[5][6][7] PRO and 4'OH PH exhibit natural fluorescence properties, permitting the use of HPLC methods with fluorescence detectors for both compounds. Other methods that have been reported include capillary electrophoresis, [8][9][10] spectrofluorimetric 11,12 and electrochemical methods. [13][14][15] A polarographic method was used to determine the quantity of PRO in pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Among various analytical methods such as chromatographic and spectrophotometric analysis, electrochemical techniques have attracted considerable interest due to the high efficiency and low cost. 9,10 However, the direct oxidation of propranolol at conventional electrodes, including glassy carbon electrodes, requires high overpotentials. Therefore, many attempts have been made to modify electrodes with some catalytic materials such as carbon nanotubes 11 and copper-oxide nanoparticles 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Drug detection is of great importance in detection and control of substance misuse, abuse, or addiction, as well as monitoring clinical effects of chronic diseases. , (±)-Propranolol hydrochloride is a β-blocker drug which is widely used to treat various cardiovascular disorders, such as angina pectoris, myocardial infarction, and hypertension cardiac arrhythmias . The rising demands for propranolol detection have driven tremendous efforts in the development of sensitive methods for quantification of propranolol in pharmaceutical formulations. Among various analytical methods, such as chromatographic and spectrophotometric analysis, electrochemical techniques have attracted considerable interest due to the high efficiency and low cost. , However, the direct oxidation of propranolol at conventional electrodes, including glassy carbon electrodes, requires high overpotentials. Therefore, many attempts have been made to modify electrodes with some catalytic materials such as carbon nanotubes and copper-oxide nanoparticles .…”
mentioning
confidence: 99%